Principles of periodization: Healthy scheduling on the women professional circuit - Stroia, K. A.; Keber, A.; Livengood, T. (Medicine and Science in Tennis, 2009)
Players must effectively and strategically plan their annual training and competitive schedules for the Sony Ericsson WTA Tour to maximize its heightened platform and for the players to reap the rewards and meet their personal performance goals. The most successful schedules and outcomes are based on the application of the principles of periodization. The Tour has a vested interest in players` health, well being and success. ´ScheduleZone´ is a tool that has been produced by the Tour to assist players in reaching their goals and enjoying a healthy and long lasting career.